Comisión de hortalizas (arveja, cebolla de rama, fríjol, haba y zanahoria). - Ortega D, Jorge; Burbano Insuasty, Edmundo E.; Angulo Ramos, Néstor F.; Martínez A, Bernardo; Villarreal, Efraín; Orbes, Manuel (Comité Regional de Producción Agrícola de Nariño, 2018)
Horticultura